2010
DOI: 10.1051/dst/2010018
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the digestion of caseins and whey proteins in equine, bovine, caprine and human milks by human gastrointestinal enzymes

Abstract: -The aim of this study was to compare the digestion of milk proteins from different species using an in vitro gastrointestinal model. Raw and heated milks from bovine, caprine, human and equine species were digested by human digestive enzymes. Digestion was performed in two 30-min sequential steps by digestive juices from the stomach (pH 2.5/37°C) and from the duodenum (pH 8.0/37°C). The degradation patterns of the milk proteins were visualized by SDS-PAGE and quantified using the ImageQuant program. Caseins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
104
2
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(129 citation statements)
references
References 27 publications
13
104
2
9
Order By: Relevance
“…This indicates that the β-lactoglobulin was completely hydrolysed by trypsin and chymotrypsin, as observed in an earlier study by Kitabatake and Kinekawa (1998). The negligible digestion of β-lactoglobulin during 1 h in the stomach at pH 1.5-7.0 has also been reported in earlier studies (Astwood et al, 1996;Chatterton et al, 2004;Inglingstad et al, 2010;Kitabatake & Kinekawa, 1998;Li, Zhu, Zhou, Peng & Guo, 2013;Sakai et al, 2000).…”
Section: Resultssupporting
confidence: 83%
“…This indicates that the β-lactoglobulin was completely hydrolysed by trypsin and chymotrypsin, as observed in an earlier study by Kitabatake and Kinekawa (1998). The negligible digestion of β-lactoglobulin during 1 h in the stomach at pH 1.5-7.0 has also been reported in earlier studies (Astwood et al, 1996;Chatterton et al, 2004;Inglingstad et al, 2010;Kitabatake & Kinekawa, 1998;Li, Zhu, Zhou, Peng & Guo, 2013;Sakai et al, 2000).…”
Section: Resultssupporting
confidence: 83%
“…Milk protein associated with allergies, gut intolerances and hyperlipidemia limit cow milk acceptability for certain groups of individuals including infants, young children, lactating mothers and the elderly (Businco et al, 2000). Donkey milk is proposed to be the best alternate in such situations and has been claimed to be highly digestible (Inglingstad et al, 2010). Donkey milk has been recommended for infants when it is not possible to breast feed and when there is no possibility to use cow milk as Copyright ©2015 ISEKI-Food Association (IFA) 10.7455/ijfs/4.…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have indicated that MM has lower allergenicity than cow's milk in children (aged 19-72 months, n = 25) with history of severe IgE-mediated CMPA based on skin prick tests (Businco et al, 2000). Inglingstad et al (2010) attributed this lower immunoreactivity to a higher digestibility of milk from equines. However, the mechanisms underlying the potential metabolic and biological effects at intestinal level remain elusive.…”
Section: Introductionmentioning
confidence: 99%